Plutocracy in the Protocol: A Quantitative Triangulation of Power Concentration in Decentralized Finance Governance - Arya Ganendra; Neva Dian Permana; Muhammad Faiz; Henry Clifford (Enigma Institute, 2025)
Decentralized Finance (DeFi) proposes a paradigm shift towards a democratized financial ecosystem governed by its users. This vision of decentralization is predicated on the distribution of governance tokens. However, the verity of this claim lacks rigorous empirical validation, raising concerns about a potential